Relationship between rs4073 polymorphism of interleukin 8 gene and cervical cancer by arms-PCR Tetra-primer - Niloufar Hashemi Sabet; Seyyedeh Mahdokht Maddah; Kumars Amini (Mashhad University of Medical Sciences, 2021)
Introduction: Cervical cancer is the second most common cancer among women. Interleukin-8 (IL-8) is a member of the chemokine family and is involved in initiating inflammatory reactions. Previous studies have shown that polymorphisms in the IL-8 gene are associated with an increased risk of various types of cancer. This study was performed with aim to investigate the association between IL-8 -251A> T polymorphism (rs4073) with cervical cancer in the female population in Tehran using Tetra primer arms-PCR. Methods: In this case-control study which was performed in 2018, a total of 100 blood samples were examined, of which 50 samples were related to women with cervical cancer and another 50 samples belonged to healthy women as a control group. After DNA extraction from all samples, the frequency of IL-8 -251A> T polymorphism (rs4073) was evaluated using Tetra primer arms-PCR technique. Data were analyzed by SPSS statistical software (version 21) and chi-square test. P<0.05 was considered statistically significant. Results: The frequency of TT, AT, AA genotypes was 42%, 50% and 8%, respectively in the patient group and 24%, 70% and 6%, respectively in the control group. The frequency of A and T alleles in the patients was 33% and 67% and in the healthy individuals was 41% and 59%, respectively. There was no significant difference between the control and patient groups in allelic distribution (P = 0.24) and genotype in all three codominant models (p=0.16), dominant (p=0.055) and recessive (P = 0.6). Conclusion: There was no relationship between IL-8 gene T-251A polymorphism and cervical cancer in the population of women studied in Tehran.